A Comparative Study of Rio de Janeiro and Johannesburg: Urbanization and Social Class - Sanchez, Sandra Siomara (Undergraduate Research Journal for the Humanities, 2016)
In the early twentieth century, two cities exhibited social unrest and social conflict. In Johannesburg, South Africa, the seeds for apartheid were sewn as an influx of workers came to nourish the country’s mines. In Rio de Janeiro, the rise of a global economy fostered immigrant communities. This paper analyzes the causes of early twentieth century social unrest as a result of the urbanization of both of these cities, and compares and contrasts both spatial and economic factors. It also investigates the labor landscapes in both cities as a supplement to these changes.